Berlian, SOJ A3 and Jawa Local Rice Varieties Phylogenetically Distinct From Oryza sativa Indica and Oryza sativa Japonica - Lathif, Yudrik; Retnaningtyas, Riri Wiyanti; Listyorini, Dwi; Suharti, Suharti (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2018)
The genetic resources identification of Indonesian local rice varieties is a crucial work should be done to conserve our native germplasm. This research aimed to know the taxonomical position of East Java local rice varieties including Jawa (JW), Berlian (BR), and SOJ A3 (SJ) using DNA barcode based on rbcL gene. Total DNA of each sample was isolated from leaves. A pair of forward 5'-ATG TCA CCA CAA ACA SJA AC-3' and reverse 5'-TCG GTA CCT GCA GTA GC-3' primers were used to amplify fragments of rbcL gene resulting in 751bp, 755bp, and 754bp fragments from BR, SJ, and JW varieties, respectively. Phylogenetic tree reconstruction revealed that our three local varieties were forming a cluster separated from the widely cultivated subspecies Oryza sativa Indica and Oryza sativa Japonica. However, further studies are necessary to reveal a more precise position of the local varieties in a phylogenetic tree on the species level.